2017
DOI: 10.17083/ijsg.v4i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ follow-up using biomechanical analysis of rehabilitation exercises

Abstract: Thanks to the evolution of game controllers video games are becoming more and more popular in physical rehabilitation. The integration of serious games in rehabilitation has been tested for various pathologies. Parallel to this clinical research, a lot of studies have been done in order to validate the use of these game controllers for simple biomechanical evaluation. Currently, it is thus possible to record the motions performed by the patients during serious gaming exercises for later analysis. Therefore, da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The mean QualSyst score is 86.42 -7.65%. Furthermore, 2017 reported the highest number of published articles (seven articles [91][92][93][94][95][96][97] ).…”
Section: Vision Systemsmentioning
confidence: 99%
“…The mean QualSyst score is 86.42 -7.65%. Furthermore, 2017 reported the highest number of published articles (seven articles [91][92][93][94][95][96][97] ).…”
Section: Vision Systemsmentioning
confidence: 99%
“…In addition, [25] found, through selecting and analyzing developed gamified systems, that there exists a tendency to develop low-cost solutions for in-home exercising with various games [8] [26]. In [27], the methodology was to use data collected during SG exercises for later analysis in order to monitor the long-term evolution of patients.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Previous studies have shown that the Kinect sensor could be used to follow patients’ evolution during rehabilitation exercises [ 26 , 27 ]. This kind of evaluation, done during the rehabilitation, has many advantages: (i) it is done in the natural environment of the patient (it is known that patients are not exhibiting the same performance when they are wearing underwear in a gait laboratory); (ii) when patients are immersed in the games they are less focused on the motion and on pain and can reach larger amplitudes than when they are asked to perform one particular motion; (iii) it provides time savings; and (iv) it is financially beneficial (the devices are affordable, and since the evaluation is done within the therapy session there is no dual pricing) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%